Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1399-0039.1989.tb01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Nco I Restriction Fragment Length Polymorphism (RFLP) of the Tumor Necrosis Factor (TNFα) region in four autoimmune diseases

Abstract: The two-allele NcoI Restriction Fragment Length Polymorphism (RFLP) of the TNF alpha region yielding bands of 5.5 and 10.5 kb was investigated in patients with systemic lupus erythematosus (SLE), pauciarticular juvenile rheumatoid arthritis (P-JRA), rheumatoid arthritis (RA) and primary Sjögren's syndrome (pSS). In all four disease, we found a decreased frequency of the 10.5 kb allele which, however, was significant only in the SLE group. In all conditions except RA, the frequency of the 5.5 kb fragment was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 11 publications
3
36
0
1
Order By: Relevance
“…TNF genotypes in each population are summarized in the Table. The observed allele frequencies were similar to those reported in the previous studies, 8,[11][12][13][14][15] and no differences were found between CHF and controls: TNFA1/TNFA2ϭ0.84/ 0.16 (CHF) or 0.84/0.16 (control) and TNFB1/TNFB2ϭ0.33/ 0.67 (CHF) or 0.32/0.68 (control). Furthermore, there were no differences in functional classes, ejection fraction, or cause of CHF by TNFA or TNFB genotypes (data not shown).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…TNF genotypes in each population are summarized in the Table. The observed allele frequencies were similar to those reported in the previous studies, 8,[11][12][13][14][15] and no differences were found between CHF and controls: TNFA1/TNFA2ϭ0.84/ 0.16 (CHF) or 0.84/0.16 (control) and TNFB1/TNFB2ϭ0.33/ 0.67 (CHF) or 0.32/0.68 (control). Furthermore, there were no differences in functional classes, ejection fraction, or cause of CHF by TNFA or TNFB genotypes (data not shown).…”
Section: Resultssupporting
confidence: 78%
“…9,12 The frequency of the TNFA2 allele increases in rheumatoid arthritis and systemic lupus erythematosus, 13 and homozygotes for the TNFA2 allele have a higher risk for death due to cerebral malaria. 14 In contrast, the TNFB2 allele decreases in systemic lupus erythematosus, 15 and homozygotes for the TNFB2 allele in severe sepsis have a higher mortality rate with higher circulating levels of TNF-␣. 11 Given the importance of TNF-␣ in the pathogenesis of CHF, we hypothesized that these genetic variations might affect susceptibility to and severity of CHF.…”
mentioning
confidence: 99%
“…In this population, the 2 308 allele was found to be associated to SLE on its own, independent of the DR3 type [45]. A NcoI Restriction-Fragment Length Polymorphism (RFLP) was first believed to be located in the TNF-a region [47,48], but was later mapped to the first intron of the TNF-b gene [49,50]. The TNFB*1 allele carries the NcoI site, while TNFB*2 does not, owing to a point mutation.…”
Section: Tnf and Tnf Receptorsmentioning
confidence: 95%
“…Studies in the mouse have indicated that a low production of TNF-a may be involved in the pathogenesis of autoimmune lupus nephritis, and that an RFLP in the TNF-a gene correlated with a reduced level of TNF-a [73]. The NcoI RFLP polymorphisms discussed in connection with SLE, have also been investigated for association to primary SS [48]. A decreased frequency of the TNFB*2 allele was found, but notably, was not significant in SS, only in SLE.…”
Section: Il-1 Receptor Antagonistmentioning
confidence: 99%
“…This hypothesis has been difficult to test because of a lack of genetic markers in the locus: an extensive search for restriction fragment length polymorphisms (RFLPs) has yielded a biallelic Nco I RFLP (10-13) and a very rare EcoRI RFLP (14). In spite of its limited information content, the Nco I RFLP has already allowed some tentative associations between TNF alleles and autoimmune diseases (11,15); recent evidence also suggests that one Nco I allele correlates with increased TNF-a and reduced TNF-13 production (13,16).…”
mentioning
confidence: 99%